GSK-3α/β Activity Negatively Regulates MMP-1/9 Expression to Suppress Mycobacterium tuberculosis Infection - Zhou, Xinying; Lie, Linmiao; Liang, Yao; Xu, Hui; Zhu, Bo; Huang, Yingqi; Zhang, Lijie; Zhang, Zelin; Li, Qianna; Wang, Qi; Han, Zhenyu; Huang, Yulan; et al. (Frontiers in Immunology, 2022)
Tuberculosis (TB) caused by Mycobacterium tuberculosis (Mtb) infection is the deadliest infectious disease and a global health problem. Macrophages (Mφs) and neutrophils that can phagocytose Mtb represent the first line of immune response to infection. Glycogen synthase kinase-3α/β (GSK-3α/β) represents a regulatory switch in host immune responses. However, the efficacy and molecular mechanisms of how GSK-3α/β interacts with Mtb infection in Mφs remain undefined. Here we demonstrated that Mtb infection down-regulated GSK-3α/β activity and promoted matrix metalloproteinase-1 (MMP-1) and -9 expressions in Mφs derived from acute monocytic human leukemia THP-1 cells (THP-1-Mφs). We confirmed the up-regulation of MMP-9 expression in tissues of TB patients compared with patients of chronic inflammation (CI). In THP-1-Mφs and C57BL/6 mice, GSK-3α/β inhibitor SB216763 significantly increased MMP-1/9 production and facilitated Mtb load, while MMP inhibitors blocked MMP-1/9 expression and Mtb infection. Consistently, GSK-3α/β silencing significantly increased MMP-1/9 expression and Mtb infection, while overexpression of GSK-3α/β and constitutive activated GSK-3α/β mutants significantly reduced MMP-1/9 expression and Mtb infection in THP-1-Mφs. MMP-1/9 silencing reduced Mtb infection, while overexpression of MMP-1/9 promoted Mtb infection in THP-1-Mφs. We further found that GSK-3α/β inhibition increased Mtb infection and MMP-1/9 expression was blocked by ERK1/2 inhibitor. Additionally, we showed that protein kinase C-δ (PKC-δ) and mammalian target of rapamycin (mTOR) reduced GSK-3α/β activity and promoted MMP-1/9 production in Mtb infected THP-1-Mφs. In conclusion, this study suggests that PKC-δ-mTOR axis suppresses GSK-3α/β activation with acceleration of MMP-1/9 expression through phospho-ERK1/2. These results reveal a novel immune escape mechanism of Mtb and a novel crosstalk between these critical signaling pathways in anti-TB immunity.